Muslims in the Western Imagination. - Arjana, Sophia Rose.
1 online resource (281 pages)
Keywords: Through an exhaustive survey of medieval, early modern, and contemporary literature, art, and cinema, Sophia Rose Arjana examines the dehumanizing ways in which Muslim men have been constructed and represented as monsters.